SISTEM PENTANAHAN DRIVEN GROUND PADA GARDU DISTRIBUSI ULP SOREANG - Fauzia Haz; Muhammad Ilhammawardi (EPSILON: Journal of Electrical Engineering and Information Technology, 2024)
In an electric power system, protection is needed that can protect and also secure users and electrical equipment, so a system is needed, namely a grounding system at the electricity distribution substation. The grounding system in the distribution network aims to directly protect people and equipment if a ground fault occurs or a current leak occurs which causes insulation failure, overvoltage on distribution network equipment and lightning can also produce fault currents and overvoltage. The danger of disturbances caused by lightning can be overcome if the grounding system is good, that is, it has a grounding resistance value of less than ≤1 ohm so that the current from disturbances caused by lightning can flow directly into the ground. Several distribution substations at ULP Soreang often experience problems because the resistance values ​​are quite high, namely 34.2 Ω, 25 Ω, 41.5 Ω, 6.42 Ω, and 10.98 Ω. The method used is a drive ground system, namely by installing a grounding rod or rod electrode into the ground to reduce the resistance value so that it can conduct excess current so that it can secure electrical equipment and maintain the safety of people who use it. The results of the research can be used as a reference in determining actions to prevent early distribution disruptions or as material for determining the installation of grounding at substations that are distributed appropriately, so that the Soreang UP3 Majalaya ULP grounding system can maintain its confidentiality.